Market information: Exporting information - Senmartin, Denise (Technical Centre for Agricultural and Rural Cooperation, 2009)
A Malian association uses communication technology to gather data from farmers to meet international export standards and then makes the same information available on the web to help supply chain partners and inform consumers.